Catching Them Early: Framework Parameters and Progress for Prenatal and Childhood Application of Advanced Therapies - Carsten W. Lederer; Lola Koniali; Tina Buerki-Thurnherr; Panayiota L. Papasavva; Stefania La Grutta; Amelia Licari; Frantisek Staud; Donato Bonifazi; Marina Kleanthous (Pharmaceutics, 2022)
Advanced therapy medicinal products (ATMPs) are medicines for human use based on genes, cells or tissue engineering. After clear successes in adults, the nascent technology now sees increasing pediatric application. For many still untreatable disorders with pre- or perinatal onset, timely intervention is simply indispensable; thus, prenatal and pediatric applications of ATMPs hold great promise for curative treatments. Moreover, for most inherited disorders, early ATMP application may substantially improve efficiency, economy and accessibility compared with application in adults. Vindicating this notion, initial data for cell-based ATMPs show better cell yields, success rates and corrections of disease parameters for younger patients, in addition to reduced overall cell and vector requirements, illustrating that early application may resolve key obstacles to the widespread application of ATMPs for inherited disorders. Here, we provide a selective review of the latest ATMP developments for prenatal, perinatal and pediatric use, with special emphasis on its comparison with ATMPs for adults. Taken together, we provide a perspective on the enormous potential and key framework parameters of clinical prenatal and pediatric ATMP application.